2011
DOI: 10.1590/s0100-879x2010007500142
|View full text |Cite
|
Sign up to set email alerts
|

E3 ubiquitin ligase Cbl-b potentiates the apoptotic action of arsenic trioxide by inhibiting the PI3K/Akt pathway

Abstract: Arsenic trioxide (ATO) is a strong inducer of apoptosis in malignant hematological cells. Inducible phosphatidyl inositol 3 kinase (PI3K)-Akt activation promotes resistance to ATO. In the present study, we evaluated whether E3 ubiquitin ligase Cbl-b, a negative regulator of PI3K activation, is involved in the action of ATO. The effect of ATO on cell viability was measured by the Trypan blue exclusion assay or by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Apoptosis was determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Yet, further studies are needed to confirm that other proteins are involved in the anti-apoptosis caspase pathway in relation to the effect of the alteration of 53BP1 in ovarian cancer cells. Coincident with our results, recent studies have shown that the downregulation of Akt has an impact on inducing G 2 /M arrest (2224). P21 waf1/Cip1 is an inhibitor of CDK (cyclin-dependent kinase) in mammalian cells and the transcriptional target of P53 (30).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Yet, further studies are needed to confirm that other proteins are involved in the anti-apoptosis caspase pathway in relation to the effect of the alteration of 53BP1 in ovarian cancer cells. Coincident with our results, recent studies have shown that the downregulation of Akt has an impact on inducing G 2 /M arrest (2224). P21 waf1/Cip1 is an inhibitor of CDK (cyclin-dependent kinase) in mammalian cells and the transcriptional target of P53 (30).…”
Section: Discussionsupporting
confidence: 92%
“…Several lines of evidence suggest that activated p-Akt serves as a multifunctional regulator of cellular processes, including cell proliferation, cell cycle and apoptosis (1921). Research has shown that modulation of the genetic background of cancer cells or therapeutic interventions may induce G 2 /M arrest accompanied by the downregulation of p-Akt (2224). …”
Section: Discussionmentioning
confidence: 99%
“…Almost all cellular processes are regulated by the ubiquitin proteasome system, including EMT [12]. Cbl-b is the second member of the E3 ubiquitin ligase Cbl family, and our group and others have revealed that Cbl-b regulates cancer cell proliferation, drug sensitivity, and migration [13-15]. Knock-down of Cbl-b enhances epidermal growth factor-induced disruption of human mammary epithelial cell adherens junctions (AJs) and cell motility [16].…”
Section: Introductionmentioning
confidence: 99%
“…Cbl-b is a second member of the E3 ubiquitin ligase Cbl family, some studies have revealed that Cbl-b regulates gastric cancer cell proliferation, drug sensitivity and also migration [1,7,8]. In addition, Cbl-b can degrade as well IGF-I signaling intermediate IRS-1 and decrease protein synthesis in unloading-induced muscle atrophy [9].…”
Section: Introductionmentioning
confidence: 99%